Current perspectives on exercise training in the management of multiple sclerosis. (2nd August 2020) - Motl, Robert W.; Sandroff, Brian M.
ABSTRACT: Introduction: The science supporting the application of exercise training and physical activity in persons with multiple sclerosis (MS) has expanded considerably in strength and scope over the past 25+ years. Exercise training is now a strategy that is commonly recommended for management of MS in clinical practice. Yet, there are still many opportunities for expanding the breadth and strength of research on exercise training in MS. Areas covered: This paper provides the authors' perspective on eight emerging areas of research involving exercise and physical activity behavior in persons living with MS. Those areas include behavior change interventions, research across the activity continuum, telerehabilitation, neuroplasticity, heterogeneity of outcomes, inclusion of targeted samples, combined interventions involving exercise training, and multi-site trials. Expert opinion: Additional research addressing those areas will greatly expand the opportunity for translation of exercise and physical activity into the clinical care of persons with MS.